Electricity consumption, urbanization and economic growth in Nigeria: New insights from combined cointegration amidst structural breaks - Solomon P. Nathaniel; Festus Victor Bekun (African Governance and Development Institute (AGDI), 2020)
The study explores the link between electricity consumption, urbanization and economic growth in Nigeria from 1971-2014. The bounds test and the Bayer and Hanck (2013) cointegration tests affirm cointegrating relationship. Electricity consumption increases economic growth in both time periods, while the impact of urbanization appears to inhibit growth. The fully modified OLS (FMOLS), dynamic OLS (DOLS) and the canonical cointegrating regression (CCR) confirm the robustness of the findings. The vector error correction model (VECM) Granger causality test supports the neutrality hypothesis in the short run and the feedback hypothesis among the variables in the long run. Therefore, policies to ensure efficient electricity supply, curb rapid urbanization and promote sustainable economic growth were suggested.
Keywords: 330; Electricity Consumption; Urbanization; Economic Growth; ARDL; Nigeria